Why do Employees Prefer to Keep Silent? Is Fear of Managers and Management's Approach Causing Employees' Silence? - Jyxhel Spahi; Rıza Feridun Elgün; Nuri Brina (Human Research in Rehabilitation, 2024)
his study aims to identify why and under what circumstances employees prefer to remain silent. The qualitative method was used to understand the reasons for the employees' silence, for which in-depth interviews were conducted. In this paper, 20 employees of the private sector in Kosovo were interviewed. Of the employees who were interviewed, seven of them are from the production sector, five from the service sector, three from the private education sector, and five from the trade sector. The interview data determined codes and categories, which were analyzed using the content analysis method. The data provided by the interview participants were analyzed through the MAXQDA 2020 qualitative data analysis program. Three categories with 21 codes mentioned in 263 cases were identified during data processing. The results show that the employees' fear of the managers and the management's approach is among the main reasons for the employees' silence. In addition, other reasons impacting employees' silence have been identified and presented in this paper.